Survei Kepuasan Muzakki Terhadap Kualitas Pelayanan BAZNAS (BAZIS) Provinsi DKI Jakarta - Mansur, Hisam; Makarim, Dina Fornia (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this study is to assess the level of satisfaction among muzakki (zakat payers) regarding the quality of service when paying zakat at BAZNAS (BAZIS) DKI Jakarta Province. It employs a quantitative research method utilizing a questionnaire. The study population consists of civil servants (ASN). The sample size comprises 890 respondents, selected through purposive sampling. Primary and secondary data is utilized for the research. The findings reveal that donors or muzakki are highly satisfied with the services provided by BAZNAS (BAZIS) DKI Jakarta Province. The lowest satisfaction score is observed in the responsiveness aspect with a score of 3.99, while the highest satisfaction score is in tangibility with a score of 4.17. It is hoped that this study can serve as a platform for further improvement of the institution, thereby influencing the public's decision in selecting BAZNAS (BAZIS) DKI Jakarta Province for their zakat distribution institution.